A Literature Review of the Factors Affecting the Compliance Costs of Environmental Regulation and Companies’ Productivity - Lenart Milan Lah; Žiga Kotnik (Central European Public Administration Review)
Purpose: The aim of the paper is to identify potential factors that influence the relative size of environmental compliance costs through a literature review and propose a conceptual holistic model of the indirect impact of these factors on companies’ productivity levels. In the literature, the connection between costs associated with environmental regulation and companies’ productivity has been thoroughly tested within what is known as the Porter hypothesis, or simply PH. Design/methodology/approach: The paper applies the methods of integrative review of scientific literature and qualitative research with a document study. Findings: The results point to several key findings. First, the identified potential factors can be divided into two main categories, namely internal factors (size, sector, age, environmental awareness, etc.) and external factors (relevance of environmental regulation for businesses, environmental stimulus measures, quality of institutions, etc.). Second, the wide use of compliance costs within the indicators of stringency of environmental regulation suggests that the relative size of environmental compliance costs is likely to affect companies’ productivity. Practical Implications: The identification of factors affecting the size of compliance costs provides valuable insights to policy makers for the implementation of environmental regulation and making it more effective while not being discriminatory in terms of presenting an excessive burden to certain types of companies. Originality/significance: There has been a gap in the literature on environmental regulation compliance costs, as so far no study has comprehensively addressed all the potential factors influencing the relative size of environmental compliance costs for companies.